Precificação de produtos financeiros de financiamento: um estudo comparativo com base em métodosde custeio - Sarah Laine de Castro (2016)
This paper is about cost based financial products pricing. Its main goal was to evaluate which costing method employed for financial product pricing best applied to a médium financial institution (FI) that operates regionally. The three following methods have been analyzed: Departmentalized Absorption Costing, Activity Based Costing and Totally Variable Costing. The concepts of each of the methods were applied in order to identify which product portfolio would bring the best operational results to the studied FI, as well as to calculate the minimum interest spread, that is, the necessary spread for meeting the operational and non-operational costs and expenses, in addition to taxes, aiming at pricing the products marketed by the FI. The choice of such methods considered, mainly, its applicability to this type of entity. The methodology started by allocating the costs of the FI to the products based on the precepts of each of the costing methods. Such allocation dictated the choice of the product portfolio and of its pricing, and was followed by a projection of results for a period of ten years. The study of the financial indicators usually employed for analyzing the performance of a FI, made it possible to evaluate which of the methods is the most efficient for supporting the process of selecting the product portfolio that will deliver the best results over time. What was shown is that the choice of the most appropriate costing method depends primarily on the cost-benefit ratio of its implementation, because even if a method is the most appropriate from a theoretical perspective, the cost and difficulty of its implementation and maintenance may encumber the company in such way that would derail it from being used over time and prevent not only the evaluation of the FIs performance, but also the very use of the method itself. That was why, after this analysis, the use of Activity Based Costing was discarded. Result evaluation also pointed that in the case of Departmentalized Absorption Costing, there is a need to establish consistent cost allocation criteria in order to avoid distortions in the comparative results. The studys conclusion demonstrated that, in accordance to the currently used criteria, the most appropriate cost method for the FI was the Departmentalized Absorption Costing, as it allows the practice of prices that are adherent to the use of the structure by each product, guaranteeing sustainability and effective financial results. Finally, it is suggested that this research is applied to other FIs in order to assess how much the cost structure and the type of the products marketed may affect the analysis of the most appropriate cost method for each one of them.